Analisis Nilai-Nilai Pendidikan Akhlak: Meneladani Tokoh Ulama Kharismatik K.H. Maimun Zubair dan Relevansinya dalam Pembentukan Karakter Generasi Z Pada Era Digital - Titi Khusnaini; Endang Ekowati; Tamyis Tamyis (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
The main objective of this study is to analyze the moral education values ??exemplified by K.H. Maimun Zubair and explore their relevance in shaping the character of Generation Z in the digital era. This study uses a qualitative approach with a library research method to analyze the moral education values ??exemplified by K.H. Maimun Zubair and their relevance in shaping the character of Generation Z in the digital era. Data were collected from academic literature, biographies, journals, and digital documents that are credible, relevant, and actual. The analysis was carried out thematically by extracting moral values, mapping their relevance to digital challenges, and synthesizing findings from various sources. This approach produces a conceptual, theoretical, and practical understanding of the character education of Generation Z and the role model of ulama in a modern context. The results of this study indicate that the role model of K.H. Maimun Zubair plays a strategic role in shaping the character and moral awareness of Generation Z in the digital era. The exemplary moral values, such as honesty, patience, discipline, empathy, and social concern, can be observed, imitated, and internalized by the younger generation. The exemplary behavior of Islamic scholars serves as a bridge between Islamic boarding school traditions and the demands of modernization, enhancing moral awareness, self-control, and the ability to make ethical decisions. These findings confirm that religious scholars who consistently exemplify morality can shape Generation Z into individuals with character, morals, adaptability, and responsibility in both real and virtual life.